The EU’s Humanitarian Policy in Africa and Migration Crisis - M. A. Kukartseva (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
The article considers the essence and peculiarities of realizing of human security in the EU external policy in general and specifically in Africa. The article reveals the principles of the EU interest in Africa as a focus of their humanitarian policy: phantoms of the collective memory of the political class of Western European countries, huge potential of resources and markets, migration and terrorist threat. It is argued that this policy is considered by the EU as its strategic foreign policy narrative, in the course of which the Union, while ensuring the security of the African continent, primarily realizes its own interests. Specific features of the interpretation of this narrative in official documents of Germany as a key member of the EU are specified. It is revealed that Germany aims to play a major role in shaping European policy towards the African continent, and the specificity of its approach is economic-centric, which distinguishes it from the EU’s general approach to Africa. The key question of the article is how is disinterested Germany’s role, despite its permeation with the spirit of liberal values as a supplier of human security to African countries. It is shown that the discrimination of refugees and migrants in migration flows in the EU emphasized the importance of the Union’s activities in ensuring human security in Africa. In accordance with its goal to become the leading actor of the EU policy on the continent, its role as a leader of the liberal world and the peculiarities of the consequences of the migration crisis for the political and party system of the country and the stability of the social state, Germany proposed the German “Marshall Plan” for Africa as a concretization of its humanitarian policy on the continent. The parameters of this Plan, its advantages and implementation difficulties are considered. It is concluded that the Germany’s approach to Africa, on the whole, indisputably contributes to the latter’s development. At the same time, it is to a large extent focused on solving the tasks of ensuring national security of Germany itself, promoting the interests of German business, creating new German “reserves” in Africa through the African partnership. In this bi-directional process there is no obvious contradiction, but the results of this process can become ambivalent.